Marine mammal demographics of the outer Washington coast during 2008 -- 2009 - Sirovic, Ana; Oleson, Erin M.; Calambokidis, John; Baumann-Pickering, Simone; Cummins, Amanda; Kerosky, Sara; Roche, Lauren; Simonis, Anne; Wiggins, Sean M.; Hildebrand, John A. (Monterey, California. Naval Postgraduate School, 2011)
In 2007 it was proposed that the U.S. Navy's Quinault Underwater Tracking Range (QUTR) off the outer Washington coast be expanded into deep water habitats (used by beaked and sperm whales) and along the coastal shelf (where coastal cetaceans forage). In 2004 an acoustic and visual monitoring effort was initiated within the boundaries of the expanded QUTR to characterize the vocalizations of marine mammal species present in the area, to determine the year-round seasonal presence of all odontocete and mysticete whales, and to evaluate the distribution of cetaceans near the Navy range. Acoustic data have been collected at two sites using autonomous High-frequency Acoustic Recording Packages (HARPs). This report summarizes acoustic data collected from June 2008 to June 2009. Seasonal occurrence and relative abundance of species consistently identified in the acoustic data are discussed in the context of earlier visual and acoustic data collections. N00244-8-1-0023.